Enhancing the BER and ACLR for the HPA Using Pre-Distortion Technique - Ehab AbdulRazzaq Hussein (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Power amplifiers are key components in wireless transceivers. Their function is to amplify signal and generate the required Radio Frequency (RF) power that allows to transmit the signal over an appropriate range. The Orthogonal Frequency Division Multiplexing (OFDM) systems are highly sensitive to nonlinear distortion introduced by High Power Amplifier (HPA). The HPA nonlinearity causes in-band and out-of-band distortions. The linearization techniques are used to compensate the nonlinear effects of the high power amplifier. These techniques correct the distortion effects resulting from nonlinearities in the transmitted signal. Many linearization techniques have been developed to improve power amplifier linearity and to decrease both Bit Error Rate (BER) and Adjacent Channel Leakage Ratio (ACLR). This work is set to run the high power amplifier in the nonlinear region. It is also attempting to analyze the resulting signal in terms of the BER and ACLR, next employs pre-distortion linearization techniques to reduce the distortion introduced in this region. According to Digital Video Broadcasting-Terrestrial (DVB-T) standard the linearization techniques, circuit and the OFDM transmitter and receiver is designed and implemented through using computer simulation of AWR Design Environment.